2010
DOI: 10.1038/ncomms1106
|View full text |Cite
|
Sign up to set email alerts
|

Overlap between folding and functional energy landscapes for adenylate kinase conformational change

Abstract: Enzyme function is often dependent on fluctuations between inactive and active structural ensembles. Adenylate kinase isolated from Escherichia coli (AK e ) is a small phosphotransfer enzyme in which interconversion between inactive (open) and active (closed) conformations is rate limiting for catalysis. AK e has a modular three-dimensional architecture with two flexible substrate-binding domains that interact with the substrates AmP, ADP and ATP. Here, we show by using a combination of biophysical and mutagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 45 publications
7
126
0
Order By: Relevance
“…Detailed analysis of the urea-dependent activation revealed that Adk can populate states with a locally disordered ATPlid domain, in accordance with a previous finding (31). This observation is also consistent with reports that the ATPlid and AMPbd domains can fold and unfold independently of unfolding of the CORE domain (8,24). In addition, we detected a strong inverse correlation between the free energy of the Adk catalytic rate (k cat ), and the free energy for substrate binding (K d ) in accordance with our previous observation of a k cat versus K M compensation effect (10).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Detailed analysis of the urea-dependent activation revealed that Adk can populate states with a locally disordered ATPlid domain, in accordance with a previous finding (31). This observation is also consistent with reports that the ATPlid and AMPbd domains can fold and unfold independently of unfolding of the CORE domain (8,24). In addition, we detected a strong inverse correlation between the free energy of the Adk catalytic rate (k cat ), and the free energy for substrate binding (K d ) in accordance with our previous observation of a k cat versus K M compensation effect (10).…”
Section: Discussionsupporting
confidence: 91%
“…Self-inducing plasmids containing wild-type Adk (23) or the I116G Adk variant (24) were transformed into BL21(DE3) cells in the presence of carbenicillin, transferred to liquid cultures and grown overnight. To label the proteins uniformly for use in 15 N-NMR applications, all variants were expressed in M9 minimal media with 15 NH 4 Cl (Cambridge Isotopes, Tewksbury, MA) as the sole nitrogen source, and purified following a previously described protocol (5).…”
Section: Protein Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this approach is useful, it is important to recall that both of these reference states can also be involved in various exchange processes that may complicate the analysis. Nevertheless, analyses of chemical shifts have provided significant insights into several systems and chemical shifts are often used as a measure of a reaction coordinate between the active and inactive states of proteins (Ådén et al 2012;Ådén & Wolf-Watz, 2007;Li et al 2008;Masterson et al 2010Masterson et al , 2011bOlsson & Wolf-Watz, 2010;Volkman et al 2001). An alternative approach for quantification of chemical shifts is the projection analysis (Selvaratnam et al 2012).…”
Section: Chemical Shiftsmentioning
confidence: 99%
“…In essence the idea is that a protein that populates two different and completely folded structural states in inactive and active conformations can transiently populate a partially disordered state in the transition state. In analogy to such 'disorder-order' transitions, cracking models can be formulated in terms of an 'order-disorder-order' event (Olsson & Wolf-Watz, 2010). Cracking is inherently difficult to probe experimentally but there are cases when its occurrence has been inferred from simulations.…”
Section: Cracking or 'Order-disorder-order' Transitionsmentioning
confidence: 99%